First Report of a Case with Needle Track Sinus after Aspiration Biopsy of a Benign Thyroid Nodule Resulted in an Unexpected Postoperative Complication. (23rd February 2010) - Dogan, Lutfi; Karaman, Niyazi; Kucuk, Ali; Ozaslan, Cihangir; Atalay, Can; Celebioglu, Sait
Abstract : Fine needle aspiration biopsy is the most feasible, safe, and accurate diagnostic tool for thyroid nodule diagnosis. The development of a sinus tract between thyroid gland and the skin through needle tract after fine needle aspiration biopsy is an extremely uncommon phenomenon. In this paper, a 71-year-old man presenting with a swelling and discharge on the anterior neck wall was reported. Similar complaints were present 15 to 20 days after fine needle aspiration biopsy of thyroid gland four years ago. Bilateral total thyroidectomy was performed considering a thyroid malignancy infiltrating the skin. Histopathologic examination confirmed a sinus tract between the thyroid gland and skin and thyroid nodule was benign in nature. It must be kept in mind that inflammatory reactions might also occur after fine needle aspiration biopsy of benign thyroid nodules. In patients with needle biopsy-related inflammation, surgery may be delayed until the inflammation subsides.